PREVALENCE OF GASTROINTESTINAL NEMATODES OF FARM ANIMALS BY COPRO-CULTURE - M. S. Al-Aboody; M. A. Omar (Российский паразитологический журнал, 2016)
In the present study, examination of 442 faecal samples was performed: 171 from cattle, 128 from buffaloes and 143 from sheep. During the period from May, 2014 to April, 2015, fecal examination showed the infection rate with abomasal nematodes was 30% in cattle, 22.6% in buffaloes, and 31.4% in sheep. Fecal culture gave results of 47.5%, 30%, and 50.3% in cattle, buffaloes and sheep respectively. Seasonal infection with abomasal nematodes as shown by faecal culture in cattle, reveals the highest infection rate is in summer (55.9%), followed by spring (54.1%), autumn (50%), and winter (33.3%). Cooperia spp. is the most prevalent larva in both cattle and buffaloes; Strongyloides papillosus is the most predominant one in sheep. Here we introduce the first study of abomasal worms infection in ruminants in Sohag, Egypt. The prevalence is found to be so high among the all examined animals, that we recommend that the authorities apply suitable control programs.